Intisari kebudayaan Brunei - Dewan Bahasa dan Pustaka (Brunei) (Bandar Seri Begawan : Dewan Bahasa dan Pustaka Brunei, 1988)
Art and culture of Brunei; papers of a seminar.
Errata slip inserted at end.
Includes bibliographical references.
In Malay
Keywords: Arts -- Brunei -- Congresses; Brunei -- Social life and customs; Brunei -- Civilization -- Congresses